Evaluation of Anti-Coccidial Activity of Different Extraction Products of Allium sativum (Garlic) in Broilers - WAQAS, M.; AKHTAR, R.; AKBAR, H.; LATEEF, M.; RASHID, I.; IJAZ, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
The present study was performed with objective to evaluate the anti-coccidial effect of three different forms of Allium sativum (garlic) in broiler birds. A total of 90 broiler chicks (day-old) were divided into nine equal groups. The mixed Eimeria species obtained from gut samples (E. tenella and E. necatrix) collected from different commercial poultry shops in Tolinton Market Lahore, Pakistan. These guts were checked in Parasitology laboratory in Department of Parasitology, University of Veterinary and Animal Sciences, Lahore. The positive cases were separated for extraction, sporulation and identification of oocyst(s). The oocysts counts per gram of droppings were determined by McMaster technique on day 0, 3, 7 and 10 of treatment. Each bird was challenged with 50,000 sporulated oocysts of Eimeria at 17th day of age. Three different forms of Allium sativum (garlic) including aqueous extract, methanol extract and powder form at dose rate 2 and 4 gm/kg body weight were used in challenged birds In all the forms and doses of the Allium sativum the oocyst per gram count was decreased but the best result was obtained with aqueous form at dose rate of 4gm/kg BW from day 7 to 10. The present study concluded that Allium sativum (garlic) can be used as natural anti-coccidial component to ameliorate the side effects and resistance of commercial anticoccidials in practice.